Emerging concepts on Leydig cell development in fetal and adult testis - Bhattacharya, Indrashis; Dey, Souvik (Frontiers in Endocrinology, 2023)
Leydig cells (Lc) reside in the interstitial compartment of the testis and are the target of Luteinising hormone (LH) for Testosterone (T) production, thus critically regulates male fertility. Classical histological studies have identified two morphologically different populations of Lc during testicular development [fetal (FLc) and adult (ALc)]. Recent progress in ex vivo cell/ organ culture, genome-wide analysis, genetically manipulated mouse models, lineage tracing, and single-cell RNA-seq experiments have revealed the diverse cellular origins with differential transcriptomic and distinct steroidogenic outputs of these populations. FLc originates from both coelomic epithelium and notch-active Nestin-positive perivascular cells located at the gonad–mesonephros borders, and get specified as Nr5a1 (previously known as Ad4BP/SF-1) expressing cells by embryonic age (E) 12.5 days in fetal mouse testes. These cells produce androstenedione (precursor of T, due to lack of HSD17β3 enzyme) and play critical a role in initial virilization and patterning of the male external genitalia. However, in neonatal testis, FLc undergoes massive regression/dedifferentiation and gradually gets replaced by T-producing ALc. Very recent studies suggest a small fraction (5-20%) of FLc still persists in adult testis. Both Nestin-positive perivascular cells and FLc are considered to be the progenitor populations for ALc. This minireview article summarizes the current understanding of Lc development in fetal and adult testes highlighting their common or diverse cellular (progenitor/stem) origins with respective functional significance in both rodents and primates.